The Average Laboratory Samples a Population of 7,300 Amazon Mechanical Turk Workers - Stewart, Neil; Ungemach, Christoph; Harris, Adam J. L.; Bartels, Daniel M.; Newell, Ben R.; Paolacci, Gabriele; Chandler, Jesse (Judgment and Decision Making, 2015)
Using capture-recapture analysis we estimate the effective size of the active Amazon Mechanical Turk (MTurk) population that a typical laboratory can access to be about 7,300 workers. We also estimate that the time taken for half of the workers to leave the MTurk pool and be replaced is about 7 months. Each laboratory has its own population pool which overlaps, often extensively, with the hundreds of other laboratories using MTurk. Our estimate is based on a sample of 114,460 completed sessions from 33,408 unique participants and 689 sessions across seven laboratories in the US, Europe, and Australia from January 2012 to March 2015.